Legal Policy for Settlement of Compensation for Land Procurement for Public Interests (Ngemplak Toll Road) - Galuh Styaningtyas Listyana Putri; Arief Budiono (Universitas Muhammadiyah Surakarta, 2023)
This study aims to determine the legal policy of settlement of compensation for land acquisition for the public interest on the Ngemplak toll road. This research is a type of descriptive research. The approach method used in this study uses an empirical juridical approach. This research was conducted at the Village Office of Donohudan Village. The data used in this study consisted of primary data and secondary data. Primary data in this study were obtained directly from interviews conducted with a number of informants consisting of the community and the government of Donohudan Village. Secondary data in this study consisted of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study found that one of the problems faced in completing compensation for land acquisition for the public interest on the Nmplak toll road is the lack of public understanding of the procedure or mechanism for compensation for land in the public interest, where there are some people who determine prices according to their own wishes without pay attention to the compensation procedure or mechanism implemented. Then, the legal policy related to the settlement of compensation for land acquisition for the public interest on the Ngemplak toll road is carried out through outreach to the community. After the socialization process was completed, the committee made a submission to the Regent. Then the Regent decides on replacement land or land or the amount of replacement money. However, if there are still residents who have not accepted the amount of replacement money proposed, the steps taken are to submit a request to the Regent for joint deliberation.